Al-Qur - M. Agus Muhtadi Bilhaq; Inayah Rohmaniyah; Salim Rahmatullah (NALAR, 2023)
The minor resurrection (qiyamah al-sugra) was generally interpreted as the death of an individual human being, meaning that when a person dies, his or her resurrection has arisen. However, in the tafsir entitled Kiamat dalam Perspektif Al-Qur